Effectiveness of Discipline Enforcement for Civil Servants in the Perspective of Legal Sociology Aspects - Purwaningsih, Irma; Prasetyoningsih, Nanik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Enforcement of civil servant (PNS) discipline is an important element in personnel management that aims to maintain the performance and integrity of government officials. However, in its implementation, the civil servant discipline system still needs to improve its effectiveness. This research aims to analyze the effectiveness of enforcing civil servant discipline from the perspective of sociological aspects of law through statutory research methods and conceptual approaches. The research method used is a juridical-normative method with a conceptual approach. Data collection was carried out through literature studies of statutory regulations, books, journals and other relevant sources. Data analysis uses content analysis techniques and legal interpretation. The research results show that the effectiveness of enforcing civil servant discipline is influenced by several factors, including clarity and firmness of civil servant discipline regulations, leadership commitment to enforcing discipline, a proportional reward and punishment system, and a supportive organizational culture. Apart from that, sociological aspects such as values, norms and social interactions that apply in the civil servant environment also influence the effectiveness of disciplinary enforcement. This research concludes that the effectiveness of enforcing civil servant discipline is not only determined by formal legal aspects but is also influenced by sociological factors that exist in the civil servant work environment. Therefore, efforts to increase the effectiveness of enforcing civil servant discipline need to consider a holistic approach that includes legal, organizational and sociological aspects.